Sejarah Pemerintahan Sultan Mahmud II dalam Kerajaan Uthmaniyyah (1808-1830 M): History of The Reign of Sultan Mahmud II in The Uthmaniyyah Kingdom (1808-1830 AD) - Mohd Bakri, Mohamad Fikri; Ishak, Muhammad Farhan (Journal Al-Muqaddimah, 2023)
Sultan Mahmud II was one of the most significant figures in the history of the Ottoman Empire. He ruled in the 19th century and faced various challenges in his efforts to restore and strengthen the empire, which was in a state of decline. This journal article discusses Sultan Mahmud II's contributions to the development of Islam, particularly in the context of the political, social, and economic changes that shaped Ottoman history. The main objective of this study is to examine Sultan Mahmud II's contributions to preserving and modernizing the Ottoman Empire and to understand their impact on the development of Islam. The study also aims to explore the steps and policies taken by Sultan Mahmud II in his efforts to address the challenges faced by the empire during his reign. This study employs a historical approach by analyzing historical sources, including relevant documents and historical writings. The analysis is conducted through a qualitative approach to understand Sultan Mahmud II's influence and contributions in the context of Islamic and Ottoman history. The study's findings indicate that Sultan Mahmud II played a significant role in modernizing the Ottoman Empire. He implemented crucial reforms in administration, the military, and the economy of the empire. These reforms had a positive impact on the development and stability of the Ottoman Empire and helped maintain Islam's position as the primary religion within the empire.